The Enterotoxicity of Clostridium difficile Toxins - Hanping Feng; Tor Savidge; Xingmin Sun (Toxins, 2010)
The major virulence factors of Clostridium difficile infection (CDI) are two large exotoxins A (TcdA) and B (TcdB). However, our understanding of the specific roles of these toxins in CDI is still evolving. It is now accepted that both toxins are enterotoxic and proinflammatory in the human intestine. Both purified TcdA and TcdB are capable of inducing the pathophysiology of CDI, although most studies have focused on TcdA. C. difficile toxins exert a wide array of biological activities by acting directly on intestinal epithelial cells. Alternatively, the toxins may target immune cells and neurons once the intestinal epithelial barrier is disrupted. The toxins may also act indirectly by stimulating cells to produce chemokines, proinflammatory cytokines, neuropeptides and other neuroimmune signals. This review considers the mechanisms of TcdA- and TcdB-induced enterotoxicity, and recent developments in this field.